Relationship between elevated impulsivity and cognitive declines in elderly community-dwelling individuals - Sakurai, Keisuke (Sci Rep, 2020)
Impulse control disorders are recognized as one of the behavioral and psychological symptoms of dementia (BPSD). Majority of studies on the treatment of BPSD related to impulsivity have rather focused on the aggression and agitation. In particular, it has not been investigated how cognitive declines are associated with impulsivity in community-dwelling elderly people. Here, we have measured the cognitive and memory functions and impulsivity of 212 elderly community-dwelling people using a psychometric test battery and analyzed the correlation between their level of impulsivity and cognitive functions by multiple regression analysis. We found an elevation of impulsivity, which was evaluated by the Barratt Impulsiveness Scale-11, closely related to decline of cognitive functions, which were evaluated by the Montreal Cognitive Assessment and the Mini-Mental State Examination, and Logical Memory function, which were evaluated by the Wechsler Memory Scale-Delayed Recall. Then we have divided them into groups based on the severity of cognitive decline and conducted an analysis of each group, the result of which showed that as this tendency was particularly noticeable in the suspected dementia group. Therefore, we have concluded that heightened impulsivity is negatively associated with cognitive and memory functions in community-dwelling elderly people.